Constituen Compound of Ethyl Acetate Fraction of Sinom Beverage Mixture of Lime and Honey (curcuma domestica val-tamarindus indica l) - Wiradnyani, Ni Ketut; Dyah Puspaningrum, Dhylla Hanggaeni (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 5 No 2 (2018): Scientific Journal of Food Technology (September), 2018)
Sinom beverage mixture of lime and honey alternative functional food. The ingredients are curcumin and young tamarin leaves as a sinom beverages mixture lime juice and honey, it is easily available, relatively in cheap that is consumed, it contains antioxidant compounds. This study aimed to identification constituen compound result of ethyl acetate fraction of sinom beverage mixture of lime and honey in vitro. With GCMS analysis of method. Ethylacetate fraction all egedly contain compounds : 1-butanamine, N-methyl-N-nitro(0,56%),  L-Sorbose  (5,96%),  3-Furaldehyde ( 0,32%), Propylcarbamate (2,95%),   2,4 Dihydroxy-2,5-dimethy1 -3(2H)-furan-3-one (1,20 %),  4H-Pyran-4-one, 3-hydroxy-2-methy1(%),  4,5-Diamino-2-hydroxpyrimidine (2,75%),  Propanal, 2,3-dihydroxy-,(S)- (3,88%), 4H-Pyran-4-one,2,3-dihydro-3,5-dihydroxyl-6-methyl-(5,04%), -Hydroxymethylfurfural (7,76 %), 3-Buten-2-one,4-(2-azido-1-hydroxy-2,6,6-trimethylcyclohexyl) butanoic acid, 3 oxo-,hexyl ester (3,28 %), N,N’- Dimethyl-1,4-butanediamine (1,05%), Epicurzerenone (0,81%), Cyclotrisiloxane, hexamethyl (4,03%),,4{2,1-} furan, dodecahydro-6,9a-dimethyl-, {3aS-(3a.alpha.,5a.alpha.,6.alpha.,9a.beta.,9b.alpha.)}  (17,90%),  -(4-Hydroxyphenyl)  -4-methyl-2-pentanone  (27,31%),   Tumerone   (2,62%),  Arsenous acid,tris (trimethylsily1) ester(5,58%). The result showed 18 constituen compound result of ethylasetat fraction of sinom beverage mixture of lime and honey. The mayor antioxidant compounds are 4H-Pyran-4-one,2,3-dihydro-3,5-dihydroxyl-6-methyl-(5,04%) and 2,4 Dihydroxy-2,5-dimethy1 -3(2H)-furan-3-one (1,20 %).